2019
DOI: 10.3126/ejdi.v25i1-2.25095
|View full text |Cite
|
Sign up to set email alerts
|

Household Fuel Transition and Determinants of Firewood Demand in Nepal

Abstract: There is an emerging challenge of providing cleaner fuel to household to avoid various health risks arising from the use of traditional non-cleaner fuel and to cope with the challenges created by climate change. The energy transition theories explain how societies switch from traditional to more advanced fuels that are cleaner and efficient. The paper examines the state of fuel transition and determinants of firewood dependence in Nepal. This paper uses data collected in 2013 from three different ecological zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the author also asserted that remittances ensure greater access to clean cooking fuels only for the lower‐middle‐income countries. Conversely, Sharma (2018) also found that international remittances are ineffective in explaining the transition from the use of the traditional firewood to the relatively cleaner sources of fuel in Nepal.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Moreover, the author also asserted that remittances ensure greater access to clean cooking fuels only for the lower‐middle‐income countries. Conversely, Sharma (2018) also found that international remittances are ineffective in explaining the transition from the use of the traditional firewood to the relatively cleaner sources of fuel in Nepal.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A study in Nepal reported a negative relation between firewood consumption and its price. 30 Similar to this, a study conducted in India in 2010 showed that households tend to depend on traditional fuel despite major share of household income being spent on energy fuel owing to the high price of clean fuel. 43 Likewise, a study of sub-Saharan Africa in 2008 reported high cost of fuel discouraging household from switching to clean cooking fuels.…”
Section: Determinants Of Household Fuel Consumptionmentioning
confidence: 62%
“…29 Other forms of household fuel such as LPG, biogas and electricity occupy a small proportion (16%) for cooking. 30 During a typical month, households were likely to use multiple sources of energy and energy switching, mixing or stacking were common depending on several factors such as availability and access to electricity, capacity to pay for the energy source and other socio-economic or cultural factors. 31 Per-capita fuel consumption in winter is double as that of other measured seasons and was attributed to greater prevalence of use and fuel consumption by supplemental stoves, not the main cooking stove.…”
Section: The Energy Ladder Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Complete replacement of TCP with a single MCS is challenging because each of these cooking solutions has unique strengths and weaknesses that drive and restrict their uptake in different geographies. Even in areas where MCS are available and affordable, households frequently own more than one cooking option and 'fuel stack' between them [24]. For example, in the high mountain regions, households often use firewood for the majority of cooking and water heating, whilst LPG is used to prepare tea and snacks [25].…”
Section: Introductionmentioning
confidence: 99%